The Academic Impacts of 2015 Nepal Earthquake: Evidence from Two Secondary Schools in Sindhupalchok District - Jeet Bahadur Sapkota; Pramila Neupane (MDPI AG, 2021)
How do natural disasters affect academic performance? Despite numerous studies having been conducted after the 2015 Nepal earthquake, the academic impacts of this tragic event have rarely been explored. Applying the OLS estimation on the microdata collected through a questionnaire survey among 189 secondary school students of two secondary schools in one of the hardest-hit rural villages, we found that students' average annual test scores dropped by 7% after the earthquake. Human losses measured by the incidence of death or injury and economic losses proxied by the level of house damage in a respondent's family were found to be significant in the decline in the annual test scores of the respondents. Because secondary schools are usually not very close for most of the students in rural mountainous communities, we controlled for time taken to reach school, which was also found to significantly increase the magnitude of the drop in the test score. However, students' level of happiness measured using the Oxford Happiness Questionnaire (OHQ) and the mother's level of education were found to be significant in reducing the magnitude of the drop in the test score of students. The findings suggest more support is needed for students who faced higher levels of human and economic loss in their family.